Mechanical response analysis of asphalt pavement considering top-down crack based on FDM-DEM coupling simulation - Min Wang; Xin Yu; Chen Chen (Journal of Road Engineering)
The occurrence of top-down (TD) cracking has gradually become a prevalent issue in semi-rigid base asphalt pavements after prolonged service. A coupled simulation model integrating the finite difference method (FDM) and discrete element method (DEM) was employed to investigate the mechanical behavior of asphalt pavement containing a pre-existing TD crack. The mesoscopic parameters of the model were calibrated based on the mixture modulus and the static mechanical response on the MLS66 test road. Finally, an analysis was performed to assess how variations in TD crack depth and longitudinal length affect the distribution patterns of transverse tensile stress, vertical shear stress, and vertical compressive stress. The results indicate that the vertical propagation of TD crack significantly increases both the tensile stress value and range on the middle surface, while the longitudinal development of TD crack has minimal impact. This phenomenon may result in more severe fatigue failure on the middle surface. With the vertical and longitudinal development of TD crack, the vertical shear stress and compressive stress show obvious ''two-stage'' characteristics. When the crack's vertical length reaches 40 ​mm, there is a sharp increase in stress on the upper surface. As the crack continues to propagate vertically, the growth of stress on the upper surface becomes negligible, while the stress in the middle and lower layers increased significantly. Conversely, for longitudinal development of TD crack, any changes in stress are insignificant when their length is less than 180 ​mm; however, as they continue to develop longitudinally beyond this threshold, there is a sharp increase in stress levels. These findings hold great significance for understanding pavement structure deterioration and maintenance behavior associated with TD crack.